Heat shock-mediated thermoprotection of larval locomotion compromised by ubiquitous overexpression of Hsp70 in Drosophila melanogaster. - Klose, M.K.; Chu, D.; Xiao, C.; Seroude, L.; Robertson, R.M. (Journal of Neurophysiology, 2005)
Maintaining the competence of locomotor circuitry under stressful conditions can benefit organisms by enabling locomotion to more tolerable microhabitats. We show that prior heat shock protects locomotion and the locomotor central pattern generator of larval Drosophila against subsequent hyperthermic stress. We combined molecular genetic, electrophysiological, and behavioral techniques to investigate heat shock-mediated thermoprotection. Prior heat shock increased the distance traveled by larvae during hyperthermia before failure. The frequency of the rhythm of peristaltic locomotor contractions and the velocity of locomotion were both less thermosensitive after heat shock and were less susceptible to failure at high temperatures. Rhythmic coordinated motor patterns, recorded intracellularly as excitatory junction potentials in body wall muscles of dissected preparations, were centrally generated because patterns could still be generated in the absence of sensory feedback (sensory function disrupted with shibire). Prior heat shock protected central circuit operation during hyperthermic stress by increasing the temperature at which it failed. Overexpression of Hsp70 after a heat shock using transgenic flies (traII) did not enhance thermoprotection, as expected, but had deleterious effects on parameters of behavior.